Diversidade Filogenética e Taxonômica de Espécies Arbóreas do Bioma Chaco: Uma abordagem para Conservação - CURIEL, Matheus Henrique; BUENO, Marcelo Leandro; FARIAS, Ivan Justino; SANTOS, Elizandra Lima dos; GUIMARÃES, Felipe da Silva; PONTARA, Vanessa (ANAIS DO ENIC, 2022)
-